1981
DOI: 10.3109/10826088109038914
|View full text |Cite
|
Sign up to set email alerts
|

Frequent Follow-up as Data Gathering and Continued Care with Alcoholics

Abstract: THe clinical value of frequent follow-up interviews as a form of continuing care for alcoholics was investigated. Sixty-seven male subjects who had participated in an inpatient alcohol research treatment study were followed up monthly for 2 years and interviewed in depth at the end of 2 years. Almost all subjects felt that the frequent follow-up contacts had functioned for them as continued supportive care. The possibility that frequent follow-up interviews may serve to consolidate and increase gains made in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

1985
1985
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 9 publications
1
22
0
Order By: Relevance
“…Additionally, there are a number of non-treatment effects likely to result in reduced drinking [19,21-23]. In order to enter the trial participants had to first achieve a level of abstinence or reduced intake.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, there are a number of non-treatment effects likely to result in reduced drinking [19,21-23]. In order to enter the trial participants had to first achieve a level of abstinence or reduced intake.…”
Section: Discussionmentioning
confidence: 99%
“…Once in the trial, the continued monitoring of drinking behavior by staff personnel may have both motivational and therapeutic benefits. For example, in one study with a 2 year follow-up [21], over half the participants indicated they liked the "caring, concern and help" follow-up telephone contact, and in another [24], the telephone interviewers reported that they usually entered in a sympathetic interaction with the study participants. Such positive empathetic contact could be of therapeutic benefit.…”
Section: Discussionmentioning
confidence: 99%
“…The potential of frequent follow-up assessment possibly to function as an active treatment has been postulated for many years (Sobell & Sobell, 1981). Assessment reactivity has become an important concern in alcohol treatment research as best illustrated by two large, comprehensively designed multiple center treatment studies: Project Matching Alcoholism Treatments to Client Heterogeneity (MATCH; Project MATCH Research Group, 1993) and Project Combining Medications and Behavioral Interventions (COMBINE;COMBINE Research Group, 2003).…”
Section: Assessment Reactivitymentioning
confidence: 99%
“…In this regard, one of the most interesting findings from Project MATCH was that even brief research contacts over the telephone appear to have the ability to support abstinence and avert relapse (see Stout et al 1999). There are some innovative and potentially effective monitoring efforts within the addiction treatment field, but these were typically developed as adjuncts to the research efforts with those patients, not as clinical interventions (Sobell & Sobell 1980;McKay et al 1998;Stout et al 1999). …”
Section: If Addiction Is Best Considered a Chronic Condition Then Wementioning
confidence: 99%